Current Electoral Processes in Southeast Asia. Regional Learnings - Facal, Gabriel (Carnets de l'Irasec, 2023)
While Southeast Asia is completing a strong geopolitical sequence and the region remains a strategic area in the relations of influence in the Indo-Pacific, several countries are also focused on electoral agendas and the domestic political dynamics they impel. The Philippines saw a presidential election (May 2022) for which an assessment has yet to be made, while the general elections in Malaysia (November 2022) and the presidential one in Timor-Leste (April 2022), followed by the legislative elections in May 2023, open up new dynamics that have yet to be consolidated. The elections showed important contrasts between countries. The results of the polls in 2023 did not lead to political renewal, but in Thailand (legislative elections, 14 May) the electoral process was marked by uncertainty, while in Cambodia (legislative elections, 23 July) it wasn't much surprise. In Indonesia (general elections in February 2024), the campaign is still open, and the results could lead to very different directions. This book, Current Electoral Processes in Southeast Asia - Regional Learnings, provides an opportunity for experts from six countries to decipher the issues and consequences of these elections (including the future ones). Moreover, based on a regional perspective, it tries to draw comparisons, parallels and contrasts, and to identify broad regional trends in the functioning of electoral systems and the political institutions on which they are based. Current Electoral Processes in Southeast Asia - Regional Learnings follows on from a seminar organised by IRASEC and Heinrich Böll Stiftung-Southeast Asia Regional Office, hosted by the Faculty of Political Science of Chulalongkorn University and with the support of the King Prajadhipok's Institute, who provided a simultaneous translation in Thai language.